Long term health complaints following the Amsterdam Air Disaster in police officers and fire-fighters. Issue 10 (27th April 2006) - Huizink, A C; Slottje, P; Witteveen, A B; Bijlsma, J A; Twisk, J W R; Smidt, N; Bramsen, I; van Mechelen, W; van der Ploeg, H M; Bouter, L M; Smid, T
Abstract : Background: On 4 October 1992, a cargo aircraft crashed into apartment buildings in Amsterdam, the Netherlands. Fire-fighters and police officers assisted with the rescue work. Objectives: To examine the long term health complaints in rescue workers exposed to a disaster. Methods: A historical cohort study was performed among police officers (n = 834) and fire-fighters (n = 334) who performed at least one disaster related task and reference groups of their non-exposed colleagues (n = 634 and n = 194, respectively). The main outcome measures included digestive, cardiovascular, musculoskeletal, nervous system, airway, skin, post-traumatic stress, fatigue, and general mental health complaints; haematological and biochemical laboratory values; and urinalysis outcomes. Results: Police officers and fire-fighters who were professionally exposed to a disaster reported more physical and mental health complaints, compared to the reference groups. No clinically relevant statistically significant differences in laboratory outcomes were found. Conclusions: This study is the first to examine long term health complaints in a large sample of rescue workers exposed to a disaster in comparison to reference groups of non-exposed colleagues. Findings show that even in the long term, and in the absence of laboratory abnormalities, rescue workers report more health complaints.